The Evaluation of the Implementation of the Recognition of Prior Learning (RPL) Program at STIA LPPN Padang Based on the Context, Input, Process, and Product Components of the CIPP Model by Stufflebeam - Naufal Raid; Ambiyar, Ambiyar; Rizal, Fahmi (The Future of Education Journal, 2025)
This study aims to evaluate the implementation of the Recognition of Prior Learning (RPL) program at STIA LPPN Padang using the CIPP evaluation model (Context, Input, Process, Product) developed by Stufflebeam. This research is an evaluative study with a qualitative approach, using data collection techniques such as in-depth interviews, observation, and document analysis. The evaluation results show that, in terms of the context, the RPL program is aligned with the institution’s vision and mission as well as the needs of the community, especially government employees in the nagari (village) in West Sumatra. In terms of input, there are certified assessors, complete RPL tools, and infrastructure support, although there are challenges in the understanding of assessments by some lecturers and limited funding. In terms of process, the implementation of socialization, portfolio assessments, verification, and credit determination has followed the guidelines, but the duration of the implementation is relatively long due to the limited number of assessors. In terms of product, the RPL program has a positive impact, including faster study progress, increased student motivation, recognition of work competencies, and contributions to the institution's reputation. However, strengthening socialization, increasing the number of assessors, and digitizing documentation are needed to improve the quality of RPL implementation in the future. This study confirms that the RPL program at STIA LPPN Padang has been effectively implemented and has the potential to further develop as a strategy for expanding inclusive and equitable higher education access.